2021
DOI: 10.3390/ma14061461
|View full text |Cite
|
Sign up to set email alerts
|

Growth of ZnO Nanorods on ITO Film for Piezoelectric Nanogenerators

Abstract: Piezoelectric nanogenerators (NGs) consist of zinc oxide nanorods (ZNRs), and polydimethylsiloxane (PDMS) layers were fabricated on indium tin oxide (ITO)-coated substrate for the energy harvesting system. The formation of seed layers by an optimized aqueous solution method greatly helped the growth of well-aligned ZNRs for NGs. Polyethylenimine (PEI) was added to increase the aspect ratio of ZNRs, which reached up to 24:1, showing the best energy harvesting performance of NGs. The formation of PDMS layers on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…It is a simple procedure that generates little heat and yields high results at a low cost. Furthermore, it is a fast and controlled technique that can produce structures that are good in terms of shape and clarity [123]. Tao et al [121] found that seed layers prepared under different oxygen partial pressure sputtering parameters and annealing treatments had a great influence on the morphology of ZnO NR arrays.…”
Section: Hydrothermal Techniquementioning
confidence: 99%
See 1 more Smart Citation
“…It is a simple procedure that generates little heat and yields high results at a low cost. Furthermore, it is a fast and controlled technique that can produce structures that are good in terms of shape and clarity [123]. Tao et al [121] found that seed layers prepared under different oxygen partial pressure sputtering parameters and annealing treatments had a great influence on the morphology of ZnO NR arrays.…”
Section: Hydrothermal Techniquementioning
confidence: 99%
“…It is a simple procedure that generates little heat and yields high results at a low cost. Furthermore, it is a fast and controlled technique that can produce structures that are good in terms of shape and clarity [123].…”
Section: Hydrothermal Techniquementioning
confidence: 99%